The manga guide to relativity - Nitta, Hideo 1957-; Yamamoto, Masafumi 1947-; Takatsu, Keita (Ohmsha ;, 2011)
This latest offering in No Starch Press's highly acclaimed EduManga series, The Manga Guide to Relativity , uses Japanese comics, clear explanations, and a charming storyline to gently introduce you to relativity. The book follows the plight of student body president Minagi, who's been sentenced to advanced physics summer school by his creepy principal. Fortunately, Minagi has the gorgeous Miss Uraga to teach him everything. The Manga Guide to Relativity begins with an overview of classical Newtonian physics before delving into Einstein's greatest discoveries. You'll learn why relativity is fu.
Print version record
Keywords: Relativity (Physics) -- Comic books, strips, etc; Graphic novels; Relativité (Physique); Bandes dessinées; Romans graphiques; graphic novels; Relativity (Physics); Physics; Physical Sciences & Mathematics; Atomic Physics; Comics (Graphic works)